MAKE EVERY WATER DROP COUNT - Bole, V S Prakasa Rao (PREPARE@u® | IEI Conferences, 2021)
Water will be the most essential commodity for the success of the ambitious 5 Trillion Economy for India. Well planned Growth in Infrastructure, Industry, Agriculture, IT, Exports etc., a lot more productive sectors will be the key factor which need sufficient water. But water is not available in abundance at present. Large parts of India are already under water stress and will face water scarcity in a few years. Since a long, Water scientists across the globe were forewarning to take urgent actions to face it. But it is being neglected by the respective stakeholders Governments / Bodies / Public etc. Minimizing wastages and improving the efficiency of water management by changing the existing water management practices is the only solution. Specific and time bound actions on the implementation of measures are required at the earliest in a mission mode to improve efficiency of water use & also adopt new technologies. This paper compiles and focuses on some issues to awaken the stakeholders to start actions. Water will become a measure of the wealth of any Country in the next few decades.